Correction and resocialization of convicts and related concepts - Denysov, S. F.; Zaika, D. Ye. (Problems of legality, 2021)
Correction and resocialization of convicts today is a stable legal structure that has been repeatedly used in legal acts and leading research. Meanwhile, historically, “correction” has been used in domestic law alongside “re-education”. “Rehabilitation” and “reintegration” are familiar to international law. The mixing and unsystematic application of the above and a number of other legal terms is not uncommon, which encourages a more detailed study of their essence and relationship between them. The article is devoted to the research of the terms “correction”, “education”, “resocialization”, “social adaptation”, “social rehabilitation” and “reintegration”. The authors set out to focus on a generalized study of: 1) the historical context, 2) the period of existence of legal relations, defined by the relevant term, 3) the essence and content, 4) features of regulation and based on analysis of the provisions of current legislation and views in the scientific literature to outline the boundaries of each of the above terms and indicate the features of their relationship. To conduct the widest possible analysis, the authors used the current legislation of Ukraine, domestic and foreign scientific literature, dictionaries, draft laws, provisions of ECtHR decisions, and documents prepared by the UN Office on Drugs and Crime. The analysis was conducted taking into account not only the criminal-executive understanding of the above concepts, but also their philosophical, social, political, medical and so on. According to the results of the research, a generalized understanding of each of these terms was formed and compared with each other. The authors came to the conclusion that the current legislation needs to be modernized and brought in line with international regulations, where instead of “correction” and “resocialization” of convicts use the terms “social rehabilitation” and “reintegration”.